Research on the Application of Hyaluronic Acid in the Treatment of Periodontal Disease - Meng, Fei; Chen, Yang (International Journal of Public Health and Medical Research, 2024)
Hyaluronic acid, as a widely used polymer material in clinical practice, has been proven to have numerous biological functions. In dentistry, the application of hyaluronic acid also has certain advantages and can be used to treat oral diseases. However, there are still many issues that need to be explored in research. Therefore, this article aims to explore the current application status and existing problems of hyaluronic acid in periodontal disease, and further test the effectiveness and safety of hyaluronic acid in the treatment of periodontal disease, in order to propose a more reasonable and effective treatment plan for periodontal disease.